Przeróbka osadów ściekowych, emisja odorów oraz możliwości ich dalszego zagospodarowania = Sewage sludge processing, odor emission and the possibilities of their future development - Zwoździak, Jerzy; Piechocka, Agata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This publication presents various approaches to waste management in relation to organic waste. The issues presented below relate to the area of constantly developing knowledge, i.e. ways to conduct technological processes in order to obtain a safe, economically optimal product.
Keywords: gospodarka osadami; gospodarka o obiegu zamkniętym; zrównoważony rozwój; uciążliwość zapachowa; sewage sludge management; circular economy; sustainbility; odor nuisance